Letter: reassuringly normal response to ACTH in children treated with swallowed topical corticosteroids for eosinophilic oesophagitis – authors' reply. Issue 12 (27th May 2019) - Philpott, Hamish; Dougherty, Michael; Torpy, David; Dellon, Evan
Abstract : Linked Content This article is linked to Philpott et al and Rodríguez Manchón et al papers. To view these articles, visit https://doi.org/10.1111/apt.14573 and https://doi.org/10.1111/apt.15243 .